The impact pf fertility decline on familial support for the elderly : An illustration from Thailand - Knodel, J.; Chayovan, N.; Siriboon, S.
tbls., gráfs.
pp. 79-103
Keywords: Fecundidad; Tailandia; Ancianos; Envejecimiento